La valoración del inventario de mercadería y el tratamiento contable según la norma internacional de información financiera para PYMES - Coyago Ajila, Mayra Alexandra (2015)
Our research work was awarded to the theme of the inventory, with respect to their accounting treatment and assessment according to IFRS for SMES, rule that the Superintendency of Companies adopted for small and medium-sized enterprises of Ecuador from the January 01 2012. The structure of the present work is composed by conceptualizing our research, analyze the context of the inventory, diagnose the needs of the enterprise to subsequently raise requirements and to delimit the proposal on the basis of the central problem, to which it has been targeted through the observation guides and the interview with the staff in charge of the area, giving us as a result of their field research, the problem that the company is not Norman treatment of inventories. Subsequently, we analyze the section 13 inventories, and with this section 27 Impairment of Assets, since these two sections are the basis for delineation of our proposal. With the guidance of bring a solution to the lack of implementation of the rules, the aim is to take the rules through an accounting policy, which will contain parameters that the staff should be governed. The development of our work in a qualitative manner, in a field investigation, using the explanatory methodology, exploratory and descriptive.